Time variability in market risk aversion - Berger,Dave; Turtle,Harry J (Journal of Financial Research, 2009)
We adopt realized covariances to estimate the coefficient of risk aversion across portfolios and through time. Our approach yields second moments that are free from measurement error and not influenced by a specified model for expected returns. Supporting the permanent income hypothesis, we find risk aversion responds to consumption smoothing behavior. As income increases, or as the ratio of consumption-to-income falls, relative risk aversion decreases. We also document variation in risk aversion across portfolios: risk aversion is highest for small and value portfolios.
Keywords: Finance